Symptomatic hypocalcemia in primary health care: review and clinical case report - Cardoso, Maria Da Graça Pereira (2022)
Introduction: Hypoparathyroidism is a cause of hypocalcemia and its main etiology is inadvertent exeresis/injury of the parathyroids during total thyroidectomy. Symptoms usually manifest in the immediate postoperative period, and it’s rare its start years after surgery. Given its nonspecific presentation, in the case of a late manifestation, the diagnosis requires a high degree of suspicion. Thus, we intend to present a case of late hypocalcemia, alerting to its non-specific symptoms and consequent difficulty in diagnosing a situation that can be potentially serious or even fatal within the scope of primary health care. Case description: Patient undergoing thyroidectomy for carcinoma, with inadvertent partial parathyroidectomy in 2010, followed by radioactive iodine therapy. Since 2016 with myalgia, paresthesia of hands, and anxiety with progressive worsening. In 2019, due to extreme anxiety and tetany of upper limbs, she was sent to the emergency department where severe hypocalcemia due to iatrogenesis after total thyroidectomy of the late presentation was diagnosed. Discussion: This is a rare condition, which can mimic a wide spectrum of diseases, musculoskeletal, neurological, or psychiatric. Trousseau and Chvostek's signs should be investigated, confirming the diagnosis with calcium and parathyroid hormone, followed by treatment with calcium and vitamin D. In acute situations, evaluation in the emergency department is necessary. This case portrays the importance of family physicians in the evaluation of nonspecific symptoms that, together with the patient’s history and careful semiological observation, may rise suspicions of uncommon, but potentially fatal, diagnoses.